1994
DOI: 10.1093/infdis/170.5.1308
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis Of Chlamydia Trachomatis Urethral Infection In Symptomatic And Asymptomatic Men By Testing First-Void Urine In A Ligase Chain Reaction Assay

Abstract: A multicenter study compared ligase chain reaction (LCR) of Chlamydia trachomatis plasmid DNA with culture of urethral swab specimens from 542 men (study A); a second study (B) compared LCR of first-void urine (FVU) with urethral swab cultures from 1043 men. Discordant results were resolved with direct fluorescent antibody staining of sediments from the FVU or urethral culture specimen and with a second LCR directed against a fragment of the major outer membrane protein gene. Test performance was calculated on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
122
1
4

Year Published

1995
1995
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(134 citation statements)
references
References 14 publications
7
122
1
4
Order By: Relevance
“…With the use of matched specimens, we have shown that, for men, urethral swabs offer no yield advantage over FVU specimens because the organism load did not differ significantly between these two specimen types (821 and 1,200 EBs/ 100 l, respectively). Our results support those of previous studies suggesting that FVU is a more practical and acceptable specimen type for detection of C. trachomatis in men and is a better diagnostic specimen for screening of asymptomatic individuals (6,8). For women, the endocervical swab has been the standard sample for most tests approved by the U.S. Food and Drug Administration.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…With the use of matched specimens, we have shown that, for men, urethral swabs offer no yield advantage over FVU specimens because the organism load did not differ significantly between these two specimen types (821 and 1,200 EBs/ 100 l, respectively). Our results support those of previous studies suggesting that FVU is a more practical and acceptable specimen type for detection of C. trachomatis in men and is a better diagnostic specimen for screening of asymptomatic individuals (6,8). For women, the endocervical swab has been the standard sample for most tests approved by the U.S. Food and Drug Administration.…”
Section: Discussionsupporting
confidence: 89%
“…Sensitivity of C. trachomatis detection with vaginal swabs has been shown to be similar to that with endocervical swabs or FVU samples (12,22,31). In men, C. trachomatis infects the urethral mucosa, which can be sampled effectively by collection of either urethral swabs or FVU, the latter being noninvasive (8)(9)(10).…”
mentioning
confidence: 99%
“…FVU specimens were collected in sterile containers and frozen at −20°C at each site until shipped to the regional virology and chlamydiology laboratory in Hamilton for testing by LCR as described previously. 5 Genotyping by restriction fragment length polymorphism (RFLP) of the outer membrane protein gene was performed at the microbiology laboratory, University of Sherbrooke, Quebec, on the specimens from first and subsequent visits of participants positive at any of the follow up visits, using previously described methods. 10 …”
Section: Laboratory Proceduresmentioning
confidence: 99%
“…4 Ligase chain reaction (LCR) testing of first void urine (FVU) to detect C trachomatis is an alternative to swab testing, especially in settings where most individuals are asymptomatic, or where patients are unlikely to agree to a pelvic examination or urethral swab. 5 Other nucleic acid amplification (NAA) tests such as polymerase chain reaction (PCR) and transcription mediated amplification (TMA) have demonstrated similar efficacy on FVU and some data are available on the role of NAA assays as tests of cure. [6][7][8] …”
mentioning
confidence: 99%
“…We therefore questioned whether the commercially available and widely used LCx assay (Abbott Diagnostics) would be appropriate for routine screening of semen specimens. The LCx assay has been developed to assess C. trachomatis infection in urine, urethral or cervical specimens and has been shown to be highly sensitive and specific (Chernesky et al, 1994;Rumpianesi et al, 1996;Watson et al, 2002).…”
Section: Introductionmentioning
confidence: 99%